Evolução geológica da região de Colméia - COSTA, João Batista Sena (Universidade Federal do Pará, 2017)
A geological mapping of the Colmeia region, in northern Goiás, has been carried out on a 1:100.000 scale. Semi-detailed geological observations coupled with stratigraphic, structural and petrological data are integrated aiming at the geological evolution of that region. The oldest recognized unit, the Archean Colmeia Complex, is represented by gneisses, granites and migmatites with associated schists, quartzites and amphibolites, and forms the central core of the Colmeia brachyanticline. Two main deformation periods have affected these rocks at the end of the Archean: the earliest period, F1deformed the rock banding surfaces into folds with E-W orlented axes and originated a well-defined axial-plane schistosity; the other one, F2, caused the refolding of the banding surfaces and folded the schistosity planes as to produce folds also with E-W oriented axes. Furthermbre, two migmatization phases were recognized: the first phase was contemporaneous with F1 and formed quartz-feldspar-rich neossomes in which minerais show a preferred orientation; the second phase predates F2 but post-dates F1, and is characterized by neossomes consisting essentially of non-oriented quartz and feldspar minerals. In the Middle Proterozoic, the Amazon Craton was regenerated leading to the accumulation of a thick volcano-sedimentary pile known as the Baixo Araguaia Super Group (Abreu, 1978). The lower unit of this pile is represented by the Estrondo Group which consists, from bottom to top of the Morro do Campo Formation (quartzites with schist intercalations), the Xambioá Formation (schists of various lithologies) and the Canto da Vazante Formation (feldspathic schists with biotite schist intercalations). The upper unit constitutes the Tocantins Group which is represented in the Colmeia region by the chlorite-quartz schists of the Pequizeiro Formation. Metamorphosed mafic and ultramafic rocks are associated with both the Estrondo and the Tocantins Group. In the Colmeia region, the Baixo Araguaia Super Group had a poliphasic evolution throughout the Middle Proterozoic. Its rocles recorded three major deformation periods: the first one is represented by intrafolial folding of the So surfaces and by the formation of an axial-plane schistosity; the second deformation event disturbed the schistosity surfaces generatinÉ folds with inclined axial planes and N-S oriented axes; the third deformation period is characterized by crenulation of the schistosity. The resulting folds have milimetric to kilometric dimensione and their axes parallel. NW-SE directions. Where the schistosity was completely transposed, crenulation cleavage was developed and biotite and chlorite recrystallizations took place on the transposition planes. The planar structures of the Baixo Araguaia basement were bent in response to shearing. Regional metamorphism of greenschist and amphibolite facies is concomitant with the first deformation episode while the second event affected the underlying Colmeia Complex superirnposing a similar folding style; at the same time contemporaneous migmatization originated N-S oriented quartz-feldspathic neossomes. Subsequent remobilization of the Colmeia Complex and the emplacement of intrusive granitic bodies gave rise to the Colmeia brachyanticline with which minor N-S oriented folds are associated. Radial faults were developed cutting both the basement and the metasedimentary cover. Other major discontinuities are also related to this event. The sedimentation of the Rio das Barreiras Formation marks the final act of the evolutionary history of the Colmeia region. Such an evolution included lithogenetic processes of the Archean and Middle Proterozoic as well as thermo-tectonic phenomena related to the Jequié and Uruaçuano cycles. K-Ar and Rb-Sr radiometric dating indicates reheating associated with the Transamazonic and Brazilian cycles.